Modulation Transfer Function of Human Visual System - KAWARA, Tetsuo; OHZU, Hitoshi (Oyo Buturi, 1977)
Modulation thresholds of the retina-brain visual system were measured with interference fringes formed by an apparatus which has been developed in our laboratory. Modulation thresholds of the foveal receptor-brain system were then calculated from these results and the MTF of the retina decided by H. Ohzu et al. It has been found that modulation sensitivities or line spread functions can be approximated by three Gaussian functions, one of which represents the excitatory high frequency response. The others represent the second excitatory and inhibitory responses at low frequency range, varying dynamically with retinal illuminance. Over-all visual system was also examined by moire fringes, and the MTFs of the eye optics were obtained. The performance of the eye optics, retina and other parts of the foveal visual system have been independently estimated. It also has been confirmed from experience of use by abnormal subjects that this technique and instrument can be applied to clinical ophthalmology.